IoT Based Automatic Medicine Dispenser with Alert System - Neeta. R. Kadam,; Chandrakant Pardeshi,; Daya Rokade,; Omkar Sawant,; Samiksha Udhane, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This work proposes an automatic medicine dispenser using the Internet of Things (IoT) with an alert system. The dispenser is controlled by an ESP32 microcontroller, which uses an RTC module to keep track of time and dispense medication at the scheduled time. Servo and stepper motors are used to rotate the medicine carousel and dispense the correct amount of medication. An LDR sensor is used to detect if the medication has been taken. If the medication is not taken, the system sends an alert to the patient's caregiver using the Blynk app. The system is powered by a battery, making it portable and convenient for use. An LCD display shows the patient the name of the medication, the dosage, and the scheduled time. A switch is used to turn the system on and off. The system has the potential to improve the medication adherence of patients, especially those who are elderly or have chronic illnesses. It can also help to reduce the workload of caregivers.
Keywords: ESP32 Microcontroller; Stepper Motor; Blynk App; LCD Display